Strategies of The Government and Laot Customary Institutions in Increasing Fishermen’s Capacity and Developing Sustainable Fisheries Businesses on Sabang Island Aceh - Muhammad Junaidi; Saprijal Saprijal; Faez Syahroni; Saddam Saddam; Agus Junaidi; Yusra Jamali; Syukran Maulana (Jurnal Community, 2025)
Sabang boasts abundant marine resources and serves as a mainstay for the fishing community. The purpose of this study was to determine the strategies of the government and traditional maritime institutions in increasing the capacity of fishermen and developing sustainable fisheries businesses. The type of research is descriptive qualitative, and data collection is carried out through documentation, interviews, and observation. Data analysis includes data reduction, data presentation, and drawing conclusions. The results of the study show that the strategy of the government and traditional sea institutions is to provide facilities, regulations, and economic improvement and provide assistance such as Big Bot, Small Bot, subsidized fuel and provision of business premises for salted fish, cracker processing, etc.The development of sustainable fisheries businesses in Sabang includes strengthening fishery product processing to absorb fishermen's production, improving supporting facilities and infrastructure such as cold storage and distribution access, and increasing the adoption of technology and institutions such as vessel registration and fishermen registration for legality and access to subsidized fuel, as well as educating fishermen in more effective and environmentally friendly fishing methods such as the use of handline fishing gear and others.